Evaluating the Surface Free Energy and Moisture Sensitivity of Warm Mix Asphalt Binders Using Dynamic Contact Angle. (3rd March 2019) - Kakar, Muhammad Rafiq; Hamzah, Meor Othman; Akhtar, Mohammad Nishat; Saleh, Junita Mohamad
Abstract : From the environmental conservation perspective, warm mix asphalt is more preferable compared to hot mix asphalt. This is because warm mix asphalt can be produced and paved in the temperature range 20–40°C lower than its equivalent hot mix asphalt. In terms of cost-effectiveness, warm mix asphalt can significantly improve the mixture workability at a lower temperature and thus reduce greenhouse gas emissions, to be environment friendly. However, the concern, which is challenging to warm mix asphalt, is its susceptibility to moisture damage due to its reduced production temperature. This may cause adhesive failure, which could eventually result in stripping of the asphalt binder from the aggregates. This research highlights the significance of Cecabase warm mix additive to lower the production temperature of warm mix asphalt and improvise the asphalt binder adhesion properties with aggregate. The binders used in the preparation of the test specimen were PG-64 and PG-76. The contact angle values were measured by using the dynamic Wilhelmy plate device. The surface free energy of Cecabase-modified binders was then computed by developing a dedicated algorithm using the C++ program. The analytical measurements such as the spreadability coefficient, work of adhesion, and compatibility ratio were used to analyze the results. The results inferred that the Cecabase improved the spreadability of the asphalt binder over limestone compared to the granite aggregate substrate. Nevertheless, the Cecabase-modified binders improved the work of adhesion. In terms of moisture sensitivity, it is also evident from the compatibility ratio indicator that, unlike granite aggregates, the limestone aggregates were less susceptible to moisture damage.